Gambaran Kesejahteraan Psikologis Guru yang Mengajar di Pesisir Pantai Lhokseumawe - Fathia, Rizka; Anastasya, Yara Andita; Muna, Zurratul (Jurnal Ilmiah Psikologi (JIPSI), 2024)
This research aims to find out the psychological well-being of teachers who teach in coastal schools. The method used in this research is descriptive quantitative. This research involved one hundred and forty seven teachers who taught on the coast using non-probability sampling techniques. The data collection method uses a psychological well-being scale modified from Setiawa & Tri's research (2014). The results of the research show that the psychological well-being of teachers who teach on the Lhokseumawe coast is relatively high with a percentage of 53.7%. This shows that the teacher's psychological well-being is able to adapt to teaching, has positive relationships with other teachers, has autonomy, can adapt to the work environment, has a life goal at work and also has good personal growth. Research based on male and female gender both have high categorization, while early adulthood has higher categorization than middle and advanced adults.